Adenoma detection rate for screening colonoscopy: one center experience - Pilvinytė, Laura; Mašalaitė, Laura; Stanaitis, Juozas (Lietuvos chirurgija, 2017)
Objective Adenoma detection rate (ADR) is a recommended quality measure for screening colonoscopies in risk population. The main aim of our study was to calculate ADR in Vilnius University Hospital Santariskiu Klinikos (VUH SK) and determine inter-individual variations among practicing endoscopists.Material and methods Retrospective data review of all the patients who underwent screening colonoscopy in the VUH SK (Vilnius, Lithuania) between 2009 and 2012.Results A total of 1633 colonoscopies, which were performed by five practicing endoscopists were included. The overall cecal intubation rate was 96.8%. Bowel preparation was good, medium and poor in 65.2%, 28.1% and 6.7% cases, respectively. Polyps were found more commonly in men rather than women: adenomas 40.4% vs. 24% (p
Keywords: adenoma; adenomatous polyps; colon; colonoscopy; detection; colorectal neoplasms